Pemanfaatan Media Film Dokumenter Dalam Pembelajaran Sejarah Untuk Meningkatkan Hasil Belajar Peserta Didik di kelas XI IPS SMA Negeri 11 Medan - Ayu, Dedek; Nugraha, Muhammad Adika; Sumantri, Pulung (Ilmu Bersama Center, 2024)
This research aims to (1) investigate how documentary films can serve as a historical learning resource for Class XI Social Studies students at SMA Negeri 11 Medan, and (2) determine whether using documentary films can improve students’ learning outcomes in history. The research employs a quantitative experimental approach, targeting the entire XI IPS cohort at SMA Negeri 11 Medan. Using purposive sampling, Class XI IPS 1 was designated as the control group and Class XI IPS 3 as the experimental group. Data collection methods included observation, multiple-choice tests, and analysis through normality, homogeneity, and hypothesis tests (t-test with a significance level of α = 0.05). The findings reveal that (1) documentary film use in history lessons significantly enhances students' learning experiences, particularly on the topic of Japan’s entry into Indonesia, by offering an engaging and visual approach. (2) There was a notable improvement in learning outcomes in the experimental group compared to the control group. The post-test average score in the experimental class was 78.69, while the control group scored 78.31. Additionally, hypothesis testing results for both classes produced a sig. (2-tailed) value of 0.000, affirming the positive influence of documentary films on students’ historical learning outcomes.